Role of Base Excision Repair Pathway in the Processing of Complex DNA Damage Generated by Oxidative Stress and Anticancer Drugs - Baiken, Yeldar; Kanayeva, Damira; Taipakova, Sabira; Groisman, Regina; Ishchenko, Alexander A.; Begimbetova, Dinara; Matkarimov, Bakhyt; Saparbaev, Murat (Frontiers in Cell and Developmental Biology, 2021)
Chemical alterations in DNA induced by genotoxic factors can have a complex nature such as bulky DNA adducts, interstrand DNA cross-links (ICLs), and clustered DNA lesions (including double-strand breaks, DSB). Complex DNA damage (CDD) has a complex character/structure as compared to singular lesions like randomly distributed abasic sites, deaminated, alkylated, and oxidized DNA bases. CDD is thought to be critical since they are more challenging to repair than singular lesions. Although CDD naturally constitutes a relatively minor fraction of the overall DNA damage induced by free radicals, DNA cross-linking agents, and ionizing radiation, if left unrepaired, these lesions cause a number of serious consequences, such as gross chromosomal rearrangements and genome instability. If not tightly controlled, the repair of ICLs and clustered bi-stranded oxidized bases via DNA excision repair will either inhibit initial steps of repair or produce persistent chromosomal breaks and consequently be lethal for the cells. Biochemical and genetic evidences indicate that the removal of CDD requires concurrent involvement of a number of distinct DNA repair pathways including poly(ADP-ribose) polymerase (PARP)-mediated DNA strand break repair, base excision repair (BER), nucleotide incision repair (NIR), global genome and transcription coupled nucleotide excision repair (GG-NER and TC-NER, respectively), mismatch repair (MMR), homologous recombination (HR), non-homologous end joining (NHEJ), and translesion DNA synthesis (TLS) pathways. In this review, we describe the role of DNA glycosylase-mediated BER pathway in the removal of complex DNA lesions.